PARENTS' PERCEPTION OF THE USE OF DIGITAL TECHNOLOGY IN LEARNING ISLAMIC RELIGIOUS EDUCATION - Laras Agustin Fajarwati (Al-Masail: Journal of Islamic Studies, 2023)
This study aims to identify parents' perceptions of the use of digital technology in learning Islamic Religious Education (PAI). The research method used a mixed methods approach, combining quantitative questionnaires from 200 parents of students in Jakarta and qualitative interviews with 20 parents. The results showed that 85% of parents found digital technology easy to use and 78% found it effective. However, only 65% felt they received adequate technical support and 70% stated the learning content was in line with religious values. Qualitative findings showed an appreciation for interactive methods, but there were concerns about internet stability and content monitoring. The novelty of this study is the holistic approach that examines parents' perceptions by considering infrastructure, technology skills and attitudes towards digital learning. This research expands the understanding of the factors that influence the acceptance of technology in religious education. The global usefulness of this study provides insights for religious education in different countries, helping policy makers and educators develop strategies for the use of digital technology in religious education, thereby improving the overall quality of education.